2020
DOI: 10.1002/da.23124
|View full text |Cite
|
Sign up to set email alerts
|

Risk of psychological sequelae among coronavirus disease‐2019 survivors: A nationwide cohort study in South Korea

Abstract: Background: We sought to investigate the risk of psychological diseases among coronavirus disease-2019 (COVID-19) survivors in South Korea. Methods: The National Health Insurance Service (NHIS) COVID-19 cohort database, comprising COVID-19 patients and a control population from January 1, 2020 to June 4, 2020, was used in this study. COVID-19 patients were defined as individuals who were confirmed as COVID-19 positive, regardless of disease severity, and COVID-19 survivors were defined as individuals who recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
3
22
1
1
Order By: Relevance
“…Using the same database (NHIS COVID-19), we recently reported that COVID-19 survivors were at higher risk of psychological sequalae. 8 However, the results of the previous study differ from those of the current study in several ways. First, the previous study was based on the database from 1 January to 4 June 2020, whereas the current study used the updated data from 1 January to 1 December 2020.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Using the same database (NHIS COVID-19), we recently reported that COVID-19 survivors were at higher risk of psychological sequalae. 8 However, the results of the previous study differ from those of the current study in several ways. First, the previous study was based on the database from 1 January to 4 June 2020, whereas the current study used the updated data from 1 January to 1 December 2020.…”
Section: Discussioncontrasting
confidence: 94%
“… 10 In South Korea, a high association of psychological sequelae in COVID-19 survivors has been reported in previous studies. 8 , 9 However, to date, studies have only evaluated the total prevalence of mental illness during a short-term follow-up period of 1 month. 9 , 11 Thus, there is an urgent need to evaluate the overall mental illness levels with a longer follow-up period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies reported symptoms in control groups, both drawn from healthy populations and neither formally matched to the respective COVID-19 groups. (36,51) Each reported higher frequencies of sleep disorder, fatigue, dizziness, depression, anxiety, and/or psychosis in COVID-19 survivors compared to controls (Table S8).…”
Section: Figure 3 and Table 2 About Herementioning
confidence: 99%
“…Rozpowszechnienie objawów PTSD u ocalonych zawierało się w zakresie od 10% [12] do 46,9% [13]. Rozpowszechnienie zaburzeń depresyjnych od 4,9% [14] do 38,1% [15]. Ryzyko śmieci samobójczej średniego stopnia rozpoznano u 22,2% ocalonych [12].…”
Section: Wstępunclassified